Studi Analitik Pola Pendidikan Karakter Oleh Luqmanul Hakim (Telaah Surah Luqman Ayat 12-19) - Nur Hafni; Fika Lutfiana; Tita Radhiya Sari; Burhan Nudin (Islamic University of Indonesia, 2021)
Character education is a conscious effort to educate and empower students tohave individual characters, attitudes, and morals in accordance with socialnorms so that they benefit themselves and society. In 2018, KPAI handled1885 cases. The most cases, 504 children, are criminal cases starting fromdrug dealers, stealing, to brawling. The KPAI also stated that the cases ofbrawl in Indonesia increased by 1.1% throughout 2018. In 2017, the number of brawl cases was 12.9%, but increased to 14% in 2018. This shows that the problem of character is one of the problems that threaten the morality, attitudes and behavior of teenagers today. This Research is a narrative literature study through a descriptive approach as a method of writing. This studyfound that the humanist method with a gradual model is the main key to the success of implementing character education. The pattern of character education in Luqmanul Hakim's story begins with the role of parents in instilling tauhid belief, the teaching to do good to parents, worship, and instilling good and noble character in a child.Keywords: Character Education, Role of Parents, Surah Luqman